2005
DOI: 10.1038/sj.ejcn.1602197
|View full text |Cite
|
Sign up to set email alerts
|

Vinegar supplementation lowers glucose and insulin responses and increases satiety after a bread meal in healthy subjects

Abstract: Objective: To investigate the potential of acetic acid supplementation as a means of lowering the glycaemic index (GI) of a bread meal, and to evaluate the possible dose-response effect on postprandial glycaemia, insulinaemia and satiety. Subjects and setting: In all, 12 healthy volunteers participated and the tests were performed at Applied Nutrition and Food Chemistry, Lund University, Sweden. Intervention: Three levels of vinegar (18, 23 and 28 mmol acetic acid) were served with a portion of white wheat bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
170
9
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(201 citation statements)
references
References 29 publications
11
170
9
7
Order By: Relevance
“…Ostman et al. (2005) also observed a significant decrease in GI when vinegar was supplemented in bread meal in a dose‐dependent manner. Compared with the reference meal, the highest level of vinegar significantly lowered the blood glucose response at 30 and 45 min, the insulin response at 15 and 30 min postprandially (Ostman et al., 2005).…”
Section: Effect Of Fermentation On Nutrients and Mineralsmentioning
confidence: 84%
See 1 more Smart Citation
“…Ostman et al. (2005) also observed a significant decrease in GI when vinegar was supplemented in bread meal in a dose‐dependent manner. Compared with the reference meal, the highest level of vinegar significantly lowered the blood glucose response at 30 and 45 min, the insulin response at 15 and 30 min postprandially (Ostman et al., 2005).…”
Section: Effect Of Fermentation On Nutrients and Mineralsmentioning
confidence: 84%
“…Some studies have reported increased (Ihediohanma, 2011; Ihekoronye & Ngoody, 1985) while others have reported decreased (Mlotha, Mwangwela, Kasapila, Siyame, & Masamba, 2016; Scazzina, Del Rio, Pellegrini, & Brighenti, 2008) GI after consumption of fermented foods. The low GI of fermented food has been attributed to the short‐chain organic acids produced during fermentation such as lactic acid, acetic acid, and propionic acid (Ostman, Granfeldt, Persson, & Bjorck, 2005). Eating lactic acid fermented foods reduced postprandial blood glucose spike (Ostman, Nilsson, Liljeberg Elmstah, Molin, & Bjorck, 2002; Scazzina et al., 2008).…”
Section: Effect Of Fermentation On Nutrients and Mineralsmentioning
confidence: 99%
“…The effect of orally delivered SCFA on appetite A number of studies investigating the effects of orally ingested SCFA, in particular acetate (delivered as vinegar) (35)(36)(37)(38) and propionate (delivered as sodium (Na) propionate) (39)(40)(41) , on subsequent satiety have been published (Table 1). These studies will be reviewed below.…”
Section: The Scfa Receptorsmentioning
confidence: 99%
“…Various studies have demonstrated positive acute effect of low-GI food, for example, increased satiety in healthy subjects (Granfeldt et al, 1994;Liljeberg and Björck, 1998;Ö stman et al, 2005) and decreased voluntary food intake in obese subjects (Ludwig, 1999). Further medium-to long-term studies in obese subjects are at hand, for example, the findings that a low-GI diet reduced fasting insulin levels in parallel to a weight loss in obese women in a 12-week study (Slabber et al, 1994), or that the body weight of obese children decreased more after a low-GI diet compared to a standard reduced fat diet in a 15-month study (Spieth et al, 2000) In the EURODIAB Complications Study of nearly 3000 adults with type I diabetes, consumption of lower GI diet was found to be related to lower measures of intra-abdominal fat mass and total body fat (waist-to-hip ratio and waist circumference) independently of carbohydrate, fat or fibre intake (Toeller et al, 2001).…”
Section: Introductionmentioning
confidence: 99%